Optimization of the elimination of antibiotics by Lemna gibba and Azolla filiculoides using response surface methodology (RSM) - Maldonado, Ingrid; Vega Quispe, Anyela Pierina; Merma Chacca, Donald; Zirena Vilca, Franz (Frontiers in Environmental Science, 2022)
Antibiotic residues are often found in aquatic sources impacted by wastewater, negatively influencing the entire aquatic biota. This research is focused on improving the antibiotic removal (tetracycline and chloramphenicol) with three factors; time (3-7 days), plants biomass (10-14 g) and antibiotics concentration (5-15 mg/L tetracycline and 10-20 mg/L chloramphenicol). For this purpose, the response surface methodology was applied, with the Box Behnken experimental design, with two plant species, Lemna gibba y Azolla filiculoides. Thus, there was one experimental design for each species; UHPLC analysis of antibiotic concentrations in water and plant samples was performed. The results indicate that both antibiotics were removed at different removal rates. Tetracycline was better removed, reaching a maximum value of 100% and 84% with Azolla and Lemna, respectively. Moreover, chloramphenicol reached 70% and 64% with Azolla and Lemna, respectively. The optimum removal values for tetracycline were as follows 6.04 d, 11.4 g, 13.4 mg/L with Lemna and 6.3, 11.9 g, 14.7 mg/L with Azolla; related to chloramphenicol 7.8 d, 13.6 g, 10.2 mg/L with Lemna, and 4.6 d, 12.3 g, 8.7 mg/L with Azolla. Concerning the Bioconcentration Factor (BCF) of antibiotics in plants, the mean values for tetracycline were 2.9% in Lemna and 4.9% in Azolla; and for chloramphenicol, 38.1% in Lemna, 37.8% in Azolla. Thus, in general, better results were obtained with Azolla.